Bioremediation of landfill gas using methanotrophic microorganisms / Jayanthi Barasarathi - Barasarathi, Jayanthi (2013)
Methane (CH4) is an important greenhouse gas with a global warming potential 25 times higher than carbon dioxide (CO2). Landfill is a one of the major contributor to global CH4 emission and is estimated to be 500-800 Mt CO2 eq/year. Previous studies have shown that microbial oxidation of CH4 in landfill cover soil can be enhanced using substrates that are rich in organic matter, such as compost. Methanotrophs are group of bacteria that utilize CH4 as its sole carbon and energy source. Therefore this study is aimed to characterize the physiochemical properties of biocover material,while identifying the potential methanotrophic bacteria from landfill cover soil. It is also intended to evaluate a comparative assessment of the CH4 efficiency of the biocover material under controlled conditions for bottle and column experiments with the addition of potential methanotrophic bacteria. Compost has been identified as best biocover material based on the associated physiochemical properties and their ability to oxidize 4% of CH4 within 4 days. Three types of methanotrophic bacteria were isolated from landfill soil and identified as Methylomonas sp, Methylococcus sp 1 and Methylococcus sp 2. Methylococcus sp 1 showed the highest CH4 oxidation capacity when compared to Methylomonas sp and Methylococcus sp 2 which took only 24 hours for complete CH4 oxidation. Batch experiment with addition of individual cultures and mixed cultures to the compost carried out at different parameters indicated higher CH4 oxidation capacity at 35˚C and 40˚C, pH 6 and at 60% v/v moisture level. Addition of Methylococcus sp 1 showed the highest CH4 oxidation activity at the rate of 8.33 X 103 μg g-1h-1 while the CH4 oxidation rate with addition of Methylomonas sp was 4.16 X 103 μg g-1h-1. Addition of Methylococcus sp 2 iii showed 75% lower activity compared to Methylococcus sp 1 and 50% lower activity compared to Methylomonas sp. Bacterial count at end of the experiment showed highest count for Methylomonas sp and Methylococcus sp 1. Statistical analysis (P <0.05) showed significant increase in CH4 oxidation with the addition of Methylomonas sp and Methylococcus sp 1 to the compost at optimum temperature, moisture and pH when compared to the control. Column experiment carried out with addition of potential methanotrophic bacteria to the compost at different column height showed highest CH4 oxidation activity at 60cm with the addition of Methylomonas sp and Methylococcus sp 1 and the comparison with control also showed 50% increase in the CH4 oxidation activity. The experiment carried out at different incubation temperature and moisture content showed highest CH4 oxidation at the temperature of 35˚C to 40˚C and 60% moisture level which are similar to batch experiment. Kinetic studies using Michaelis Menten equation for batch experiment at optimum parameters showed highest potential CH4 oxidation rate with the addition of Methyloccocus sp 1. Addition of methanotrophic bacteria to compost showed an enhancement and significant increase in the CH4 oxidation under optimum parameters which are also similar to tropical conditions. A biocover with 60cm column height is potentially the best height for optimal CH4 oxidation.